National Consultation for Improving Climate Services in Tanzaniam - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
This three day workshop identified the institutional and operational needs, gaps and capacities for climate services in the agriculture, food security, health and disaster risk reduction sectors in Tanzania. Photo: V. Atakos (CCAFS)